2017
DOI: 10.1515/mjss-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Investment Climate on Total Factor Productivity of Manufacturing Industries in Nigeria

Abstract: This study examines the influence of investment climate on productivity of manufacturing industries in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In recent years, the issue of economic operating environment that restricts enterprise growth has come to the center stage in most academic conversation in a bid to improve productivity and efficiency. With this view [49] explored the impact of investment environment on manufacturing productivity in Nigeria, the results show that power outage, loss in transit due to breakage or spoilage and tax burden have a significant negative effect on total factor productivity of manufacturing industries in Nigeria. Similarly [50] studied the efficiency of energy intensive industries across European countries based on Data envelopment analysis (DEA) combined with Malmquist productivity index (MPI) and found that the high electricity prices, energy taxes have a negative effect on industrial efficiency.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In recent years, the issue of economic operating environment that restricts enterprise growth has come to the center stage in most academic conversation in a bid to improve productivity and efficiency. With this view [49] explored the impact of investment environment on manufacturing productivity in Nigeria, the results show that power outage, loss in transit due to breakage or spoilage and tax burden have a significant negative effect on total factor productivity of manufacturing industries in Nigeria. Similarly [50] studied the efficiency of energy intensive industries across European countries based on Data envelopment analysis (DEA) combined with Malmquist productivity index (MPI) and found that the high electricity prices, energy taxes have a negative effect on industrial efficiency.…”
Section: Review Of Related Literaturementioning
confidence: 99%